Electrophilic additions to unsaturated systems - De la Mare, Peter Bernard David; Bolton, R. (Roger) (Elsevier Scientific Pub. Co, 1982)
The first edition of this book, published in 1966, received wide acclaim. This new edition has been almost entirely rewritten and expanded to incorporate the extensive research done in this field over the last two decades. The book provides a unified treatment, from a mechanistic viewpoint, of those reactions of unsaturated organic compoiunds which, being initiated by co-ordination with an electrophilic reagent, proceed through intermediates having cationic character, and are completed by the formation of products of addition. After a brief account of the properties of carbocations, electrophilic reagents are considered in accordance with their position in the Periodic Table of the elements.